Prevalence and in vitro antifungal susceptibility of Candida spp isolated from clinical specimens in São Paulo, Brazil - Sugizaki, Maria Fátima [UNESP]; Rhoden, Cristianne Roberta [UNESP]; Bombonatti, Denise Mara [UNESP]; Montelli, Augusto Cezar [UNESP]; Martinson, Margarida Eleonora [UNESP]; De Magalhaes Lopes, Carlos Alberto [UNESP] (My University, 1998)
We examined the prevalence and the in vitro susceptibility to antifungal drugs of Candida spp isolated from clinical specimens at our university hospital in São Paulo, Brazil. Among 6,417 samples studied, positive cultures, were obtained from 222 (3.5%) most of them (68%) from the pediatric unit and nursery. Candida albicans and Candida parapsilosis were the most frequent species and the susceptibility patterns of a panel of 130 isolates to amphotericin B, ketoconazole and fluconazole. showed that the order of antifungal efficacy was amphotericin B > ketoconazole > fluconazole.
Keywords: Antifungal susceptibility; Brazil; Candida spp; Prevalence